“Blue Sky Effect”: Contextual Influences on Pupil Size During Naturalistic Visual Search - Thurman, Steven M.; Cohen Hoffing, Russell A.; Madison, Anna; Ries, Anthony J.; Gordon, Stephen M.; Touryan, Jonathan (Frontiers in Psychology, 2021)
Pupil size is influenced by cognitive and non-cognitive factors. One of the strongest modulators of pupil size is scene luminance, which complicates studies of cognitive pupillometry in environments with complex patterns of visual stimulation. To help understand how dynamic visual scene statistics influence pupil size during an active visual search task in a visually rich 3D virtual environment, we analyzed the correlation between pupil size and intensity changes of image pixels in the red, green and blue (RGB) channels within a large window (~14 degrees) surrounding the gaze position over time. Overall, blue and green channels had a stronger influence on pupil size than the red channel. The correlation maps were not consistent with the hypothesis of a foveal bias for luminance, instead revealing a significant contextual effect whereby pixels above the gaze point in the green/blue channels had a disproportionate impact on pupil size. We hypothesized this differential sensitivity of pupil responsiveness to blue light from above as a “blue sky effect”, and confirmed this finding with a follow-on experiment with a controlled laboratory task. Pupillary constrictions were significantly stronger when blue was presented above fixation (paired with luminance-matched gray on bottom) compared to below fixation. This effect was specific for the blue color channel and this stimulus orientation. These results highlight the differential sensitivity of pupillary responses to scene statistics in studies or applications that involve complex visual environments, and suggest blue light as a predominant factor influencing pupil size.